“The Role of Extracurricular Activities in Developing Students’ Modern and Innovative Competencies” - Djabbarova Nargiza Bakitovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the significance of extracurricular activities in schools for developing students’ modern and innovative competencies. The study examines how interactive methods, project-based learning, and digital technologies can enhance students’ creative thinking, independent learning, and problem-solving skills. Emphasis is placed on the pedagogical advantages of integrating innovative approaches into extracurricular activities to foster motivation, engagement, and overall academic growth.